Empathy map of postgraduate students on information science: A reflection on the relationship between students and digital humanities - Calegari Crispim, Adriana; dos Santos Bahia Jacintho, Eliana Maria (Advanced Notes in Information Science, 2023)
The digital humanities (DH) subject is a significant opportunity to learn about what encompasses DH for the postgraduate academic community. This research aimed to observe the DH discipline and its students of the postgraduate course in Information Science at the Federal University of Santa Catarina. This is an exploratory, descriptive character of a qualitative nature. The empathy map model, developed by Xplane, was used to analyze the results. From this research model, it was possible to understand and explore the real expectations and thinking of students attending the DH course.